Global futures : shaping globalization - Nederveen Pieterse, Jan. (London ; New York : Zed Books ; New York, N.Y. : Distributed in the USA by St. Martin's Press, 2000)
"This is the first book to go beyond globalization. Its eminent contributors reject a fatalistic stance in the face of the problems that accelerating globalization is throwing up. Instead, they argue that humanity must make seek to shape globalization. In a sequence of tightly argued essays, they suggest a variety of innovative perspectives, changes, policies and institutional reforms that we ought to strive for in our increasingly inter-connected world. The exciting range of topics discussed include global governance and democratization; international finance and reform of the world economy; Third World development; the environment; the position of women; poverty and social exclusion; technology and culture; and the future shape of urban growth. Optimistic and inventionist in tone, this book provides a one-stop overview of thinking about global reform. Bristling with ideas, its new angle on globalization brings together different domains of transformation and different disciplines, looking to a future in which humanity consciously influences, improves and humanizes what may otherwise be seen as an impersonal and destructive juggernaut."--Back cover.
Shaping globalization / Jan Nederveen Pieterse -- Humane governance for the world: reviving the quest / Richard Falk -- Globalization: a developmental approach / Jan Pronk -- World economic changes at the threshold of the twenty-first century / Louis Emmerij -- Life beyond global economic warfare / Hazel Henderson -- The mosaic of global taxes / Howard M. Wachtel -- An alternative to global marketization / Sakamoto Yoshikazu -- The local dimensions of global reform / Fantu Cheru -- Poverty and the politics of alternatives at the end of the millennium / Michael Watts -- Environmental justice as a force for sustainability / Joan Martinez-Alier -- Feminist futures / Azza M. Karam -- Culture and economic growth: the state and globalization / Keith Griffin -- Technologies of post-human development and the potential for global citizenship / Mike Featherstone -- Cities: contradictory utopias / Anthony D. King.
Includes bibliographical references and index.
Keywords: Social prediction; Economic forecasting; Progress; Culture; International economic relations -- Sociological aspects; Globalization